Genetic analysis of multiple-stress tolerant extra-early maize (Zea mays L.) inbred lines under contrasting environments - Obisesan, O.I. (Obafemi Awolowo University, 2021)
This study evaluated grain yield performance and stability of 210 extra-early maize hybrids across stress and non-stress environments; established the mode of gene action controlling the inheritance of yield and other traits under Striga infestation, drought, optimal conditions and across environments; assessed the combining abilities of the inbreds; classified the lines to heterotic groups based on their combining ability; and determined the efficiency of inbred testers and interrelationship among traits measured. These were with a view to develop and deploy improved hybrids with combined tolerance to these stresses in West and Central Africa. Thirty-nine inbred lines were crossed to five inbred testers to generate 195 testcrosses. Ten single-cross hybrids were also generated by crossing the five testers in a diallel fashion. The 205 testcrosses were evaluated with five hybrid checks using a 14 x 15 lattice design under drought, artificial Striga infestation and optimal growing environments. In all evaluations, data were collected on yield and other agronomic traits. All data were subjected to analysis of variance to test for significant variation among genotypes and partition total genotypic effect into additive and non-additive components. Genotype main effect plus genotype by environment interaction (GGE) biplot analysis was employed to identify high-yielding and stable hybrids. Relationship among traits under each environment was assessed using path coefficient analysis. Significant (P ≤ 0.05) genetic variability for yield and other traits was obtained under each and across environments. Across research conditions, TZEEI 254 x TZEEI 29, TZEEI 377 x TZEEI 29 and TZEEI 243 x TZEEI 13 were high-yielding and most stable. Both GCA and SCA mean squares were significant (P<0.05) for grain yield under all research environments. While additive gene action was preponderant over non-additive for grain yield under Striga, non-additive gene action was preponderant over additive for grain yield and most other measured traits under drought, optimal and across stress environments. Eight inbreds under Striga infestation, two under drought, four under optimal and four across stress environments had significant positive GCA effects for yield. Of the five testers, TZEEI 21, TZEEI 29 and TZEEI 13 were efficient across stress environments. Inbreds were classified into four groups each under the two stress environments, and three groups each were identified under optimal and across stress environments. Path coefficient analysis identified ear aspect (-0.8), Striga damage rating (-0.1) and ears per plant (0.095) under Striga, ear aspect (-0.6), days to silking (-0.2), days to anthesis (-0.2) and stay-green characteristics (-0.1) under drought, ears aspect (-0.5), ears per plant (0.2), plant aspect (-0.2), root lodging (0.1) and stem lodging (0.1) had significant direct effects on yield. The study concluded that inbreds TZEEI 253 and TZEEI 386, and hybrids TZEEI 254 x TZEEI 29, TZEEI 377 x TZEEI 29 and TZEEI 243 x TZEEI 13 were promising multiple stress tolerant maize, and would be invaluable resources for improving maize productivity in the subregion.